MEDIATING THE GREEK-TURKISH CONFLICT: THE EFFICACY, CHALLENGES, AND INNOVATIVE PATHWAYS OF NATO’S INTERNAL MECHANISMS - Jie, Sun (PEOPLE: International Journal of Social Sciences, 2024)
The ongoing conflict between Greece and Turkey poses significant challenges to regional stability, highlighting the critical role of NATO in mediating such disputes. This paper examines the efficacy of NATO’s internal mechanisms in mediating the Greek-Turkish conflict, identifies the key challenges these mechanisms face, and explores innovative pathways for resolution. Employing a mixed-methods approach that includes a literature review, case studies, and comparative analysis, we uncover the strengths and limitations of NATO’s current conflict resolution strategies. Our findings reveal that while NATO’s mechanisms have facilitated dialogue, political divergences among member states and external geopolitical pressures have often hindered effective mediation. The paper proposes innovative solutions, including enhancing preemptive conflict management tools, establishing more inclusive dialogue platforms, and incorporating technology in mediation processes. These suggestions aim to bolster NATO’s role in the Greek-Turkish context and future international conflicts, contributing to a more stable and peaceful international order.